2019
DOI: 10.3389/fpsyg.2019.02067
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Psychometrics of Career Decision Ambiguity Tolerance Scale

Abstract: This study aimed to validate career decision ambiguity tolerance scale-Korean form applicable to a Korean sample. In study 1, 17-items from the original 18-item career decision ambiguity tolerance scale were valid based on IRT. In study 2, using the confirmatory factor analysis, we showed that excluding item 4 from the original scale is better than including it in the three factors model. Given the results of study 1 and 2, the constructs in the 17-item career decision ambiguity tolerance scale-Korean form wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…We used Cronbach’s α , McDonald’s ω (for subscales consisting of at least three items, Tables 3 – 5 reported in Supplementary Material ) and Mokken scale analysis (coefficient H ) to assess the properties of the subscales of the BIAS map. Mokken scale analysis is used to investigate psychometric properties of a scale, comparing its actual Guttman errors to expected errors (resulting in scalability score) and assessing “whether each item evaluates the same underlying concept” ( Park et al, 2019 ). When assumptions are violated, the omega coefficient provides a better assessment of the internal consistency (reliability) of a scale than the alpha coefficient does ( Dunn et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…We used Cronbach’s α , McDonald’s ω (for subscales consisting of at least three items, Tables 3 – 5 reported in Supplementary Material ) and Mokken scale analysis (coefficient H ) to assess the properties of the subscales of the BIAS map. Mokken scale analysis is used to investigate psychometric properties of a scale, comparing its actual Guttman errors to expected errors (resulting in scalability score) and assessing “whether each item evaluates the same underlying concept” ( Park et al, 2019 ). When assumptions are violated, the omega coefficient provides a better assessment of the internal consistency (reliability) of a scale than the alpha coefficient does ( Dunn et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Third, participants in Study 3 were required to rate the measure two times over a 4-week period to confirm the test–retest reliability of the measure. Considering that 4 weeks is a relatively short time interval and may lead to a carryover effect due to memory or practice ( Allen and Yen, 2001 ; Park et al, 2019 ), future studies should extend the time interval to strengthen the reliability of our scale.…”
Section: Discussionmentioning
confidence: 99%
“…The time lag of 4 weeks is appropriate to explore the stability of the measurement, since a 4-week interval is long enough to allow the variability in individuals’ attitudes and behaviors but also is short enough to allow some stability in individuals’ lives ( Daniels and Guppy, 1994 ; Ouweneel et al, 2011 ). Additionally, previous studies (e.g., Park et al, 2019 , 2021a ) have demonstrated the test–retest reliability of their measurements using a 4-week interval.…”
Section: Study 3: Test–retest Reliabilitymentioning
confidence: 95%
See 1 more Smart Citation
“…The CDAT has good structural and construct validity (Xu & Tracey, 2015b). The instrument has been validated or used in several cultures and countries, such as France (Storme et al, 2019) which is high in individualism and uncertainty avoidance dimension, South Korea (Park et al, 2019), which is low in individualism but high in uncertainty avoidance dimension, and China (Xu et al, 2016), which is low in individualism and uncertainty avoidance aspect. In individualistic societies, individuals are expected to prioritize and take care of themselves and their direct family, but in collectivistic settings, individuals belong to 'in groups' that care for them in exchange for a certain level of loyalty.…”
Section: Introductionmentioning
confidence: 99%